The Maqasid Al Shariah and the Sustainability Paradigm: Literature Review and Proposed Mutual Framework for Asnaf Development - Al Haq, M Ashraf; Abd Wahab, Norazlina (CSRC Publishing, 2019)
The study examines through analysing the literature, that the zakat recipients (asnaf) can be better entertained by a sustained mechanism than one-off measures. The main aim towards asnaf upliftmentshould be based on a self-reliance goal-oriented-action strategy plan to alleviate them from any further deprivation. The aim of Maqasid in addressing these issues is to ensure that an asking basket gets smaller day by day through an effective regime. Design/Methodology/Approach -The paper analyses and synthesises the relevant literature on Maqasid and sustainable paradigm, then proposes a conceptual convergence to understand the paradigmatic similarities between the two in appreciating the welfare of zakat recipients. Findings -The paper attempts to examine the latitude of sustainability and Maqasid necessities in relation to asnaf welfare. The sustainability development?s main concern that the future generation benefits from the present development, which is quite similar to Hifzul Nasl or protection of progeny in Maqasid fulfilment. It can be stated that the three jurisdictions of sustainable development (SD) paradigm i.e., namely, the social, economic and environmental concerns are in actual fact, more in conformity with the Maqasid requirements. But many authors stated that indeed Maqasid is more wholesome and more encompassing than the traditional SD paradigm. Islam categorically highlights that human being as a caretaker of environment, need to ensure a better, and harmonious society, that should be erected with constructive and productive economic activities and not resorting to any damages to the nature. These concerns clearly conforms with Maqasid when it conditions that the protection of life orhealth, or intellect or progeny or wealth needs to be with true understanding about the self as well as the kindness of the creator, which truly encompasses faith, and that to achieve any higher dimension,may require that these basic necessities are fulfilled and ascertained at the foremost.Originality/value -This study scrutinises a comprehensive understanding about sustainability and Maqaisd needs in addressing the asnaf development and welfare. The study further elucidates that even the nature is in constant salutation towards thanking the Lord for all the bounties